Checklist of treehoppers of Panama (Hemiptera: Membracidae) with a list of checklists and keys to the Nearctic and Neotropical fauna - Flynn, Dawn J. (Zootaxa, 2012)
A checklist of treehoppers (Hemiptera: Membracidae) of Panama is provided with known province distribution data. The worldcatalogue of Membracoidea, through 1996, lists 68 genera, 162 species, and 1 subspecies from Panama (McKamey, 1998).New research in Panama has documented range extensions for 29 genera, 107 species, and 1 subspecies previously unknownfrom Panama. With these adjustments and additions, the total treehopper fauna from Panama includes 97 genera, 269 species, and 2 subspecies. Tables listing published checklists and keys for Nearctic and Neotropical treehoppers are presented.